Nanocomposite sensors with indium tin oxide nanowires in a polyvinyl butyral matrix for crack detection in structural health monitoring - Preto, Eduardo [UNESP]; Ambrozini, Beatriz [UNESP]; da Silva, Samuel [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (SAGE Publications, 2025)
We propose and test a novel sensor for structural health monitoring (SHM) based on a nanocomposite film consisting of indium tin oxide (ITO) nanowires embedded in a polyvinyl butyral (PVB) matrix to detect cracks. The sensor operates by measuring the electrical resistance between terminals when it is adhered to the surface of a structure. When damage mechanisms are present, the ITO nanowires either break or rearrange, causing a change in the sensor’s internal resistance. However, certain limitations must be addressed for broader applications. Among these, the effects of loading, humidity, and temperature fluctuations in the host structure pose significant challenges. Experimental tests were conducted to evaluate the environmental influences on measurements, revealing minimal data variation, indicating that these factors are not critical concerns. Additionally, sensitivity tests were performed to assess the sensor’s response to structural changes emulating damage mechanisms, and the sensor demonstrated accurate detection. In crack propagation experiments, the sensor detected cracks during their nucleation, propagation, and ultimate failure stages. The results show this novel sensor has strong potential for crack detection and monitoring applications. Another key advantage is the simplicity of signal collection and analysis, as measurements can be obtained through static readings without excitation signals in the structure. Furthermore, the sensor’s resistance correlates well with the extent of damage.
Keywords: crack propagation; ITO; nanocomposite sensor; PVB; resistance variation; SHM